Profiteering from Urban Safety, Fear of Crime and Earthquakes in Istanbul - Halil Ibrahim Bahar (International Journal for Crime, Justice and Social Democracy, 2019)
There is a direct relationship between urban safety in Istanbul and neoliberal urban planning policies that has led to the creation of a new wealthy class. Such a class has risen from profiteering from land deals and the construction of housing and offices, both of which were politically facilitated. The classification of areas of the city as being at risk from crime and earthquake, together with the legalisation of urban change projects, have resulted in whole sections of the community being declared at risk and moved to other areas with an attendant rise in social exclusion.